“If he could speak, he would be able to point out who does those things to him”: Experiences of violence and access to child protection among children with disabilities in Uganda and Malawi - Banks, Lena Morgon (PLoS One, 2017)
INTRODUCTION: There is growing evidence that children with disabilities face an increased risk of violence globally. While child protection mechanisms to prevent and respond to violence–including formal government systems and more informal programmes and activities run by local communities or NGOs–are slowly becoming operationalised in low- and- middle-income countries, little is known about whether existing mechanisms are disability-inclusive. The aim of this study is to provide a better understanding of children with disabilities’ experiences of violence and their access to available child protection mechanisms in low resource settings. METHODS: This study was conducted in Kasungu and Mulanje districts in Malawi and Kamuli district in Uganda between October-December 2015. In-depth, semi-structured interviews were conducted with approximately 20 purposively selected child/caregiver pairs in each country (43 pairs total). Interviews with key informants involved in the provision of child protection and disability support were also conducted. All interviews were recorded, transcribed and coded in NVivo. Thematic Analysis, complemented by constant comparison as described in Grounded Theory, was used to analyse the data. RESULTS: Almost all children with disabilities reported experiencing violence, with verbal abuse and bullying the most common forms. Very few of these children sought recourse through available child protection mechanisms. Some of the key factors impeding access to child protection for children with disabilities included: lack of local government disability-inclusive planning and budgeting; centralization of limited disability and social protection services; financial barriers to seeking and receiving care; and stigma and negative attitudes toward disabilities. CONCLUSION: Children with disabilities face both high levels of violence and high barriers to accessing available child protection mechanisms. There is an urgent need to ensure that all efforts to prevent and respond to violence against children are more disability-inclusive. In addition, it may be appropriate to target child protection mechanisms specifically toward children with disabilities because of the different and intersecting vulnerabilities that they face.